Structural adjustment, the environment, and sustainable development - Reed, David, 1948 July 24- (London : Earthscan, 1996)
"Structural Adjustment and the Environment (Earthscan, 1992) was the first book to fully examine the effects of 'structural adjustment programmes' - the economic reform policies required by the World Bank and IMF as part of their lending operations with borrowing countries. To widespread critical acclaim it exposed the damaging environmental and social effects of structural adjustment policies, and called for a thorough revision of the then-current development policy." "This new work, Structural Adjustment, the Environment and Sustainable Development, is a major step forward in the study of structural adjustment policies. It looks in detail at new research and analysis into their effects, and incorporates recent studies by a wide range of academics and policy-makers, leading experts and institutes. Focusing on nine in-depth case studies, the book examines the complex links between macroeconomic policies, social impacts and environmental outcomes, and takes a forward-looking perspective in outlining the alternatives to current structural adjustment policies."--Jacket
Includes bibliographical references (p. [367]-373) and index.
Keywords: Structural adjustment (Economic policy) -- Developing countries -- Case studies; Environmental policy -- Developing countries -- Case studies; Sustainable development -- Developing countries -- Case studies